Internalization of Cooperation Value in Drum Band Extracurricular Activities - Raihanatul Jannah; Khairunnisa Khairunnisa; Nurlaili Fitri (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to define the internalization of cooperation value in drum band extracurricular activities, as well as the supporting and inhibiting factors in its process. This study uses field research (field research) using a qualitative descriptive method. Data collection techniques in this study are observation, interviews, and documentation. Data processing techniques in this study include data editing, classification, and interpretation. While the subjects of this study are school principals, trainers, teachers, parents, and students. The study results show that the internalization of cooperation value has been applied to drum band extracurriculars in the form of group exercises, group exercises, and joint exercises, effective communication, openness, shared responsibility, and understanding of common goals. The supporting and inhibiting factors in this internalization process include trainers, students, parents, classrooms, fields, funds, and infrastructure. The implications of internalizing the cooperation value in the drum band extracurricular are 1) it makes it easier for teachers to convey material, 2) it makes it easier for students to memorize material, 3) students are more enthusiastic about participating in activities, 4) makes it easier for students to practice cooperation and cohesiveness, 5) the sound of the music produced is better because of their solid cooperation, 5) form an attitude of cooperation and mutual help and benefit for the future. Education practitioners need to develop a mature strategy to internalize character values in extracurricular activities and minimize obstacles to get maximum results.